Entre a escravidão e a liberdade em Vitória/ES (1871-1920) - Nunes, Rafaela Domingos Lago (2018)
The thesis consists of the study of the problem of the after-abolition, with emphasis in the social relations of captives and egresses of the captivity in the region of Vitória, during the years of 1871 and 1920. The objective of the study was to understand the socioeconomics changes, responsible in great length for the demographic drawing of the central and southern regions of the state of Espirito Santo, in the period been screen. A research to sea liberation of the slaves with the advent of the emancipationist laws (1871 and 1885), and the abolitionist (1888) transformed the consolidated constructed communities for generations in the captivity, on between itself for extensive nets of kinship. The temporal landmarks are delimited by the year in which the Law of the Free Womb was promulgated in 1871, and the year of 1920, which ended the height of the racist thought in Brazil, reflecting the consequenc es of the crisis in the coffee bean prices that occurred in the two previous decades. Responsible to speed up the process of constitution in the agrarian structure of small small properties in the State of Espirito Santo. They utilized baptisms and birth certificates, a known source of research in the region. Emancipate letters, provincial reports of directors of the State, funds of government and newspapers published in Espirito Santo are added it the document body. The comparative analysis with the previous period to the one of 1871 allowed observing an intensification in the social relations of the captives with non-captives from the Law Rio Branco. That is, slave families took advantage of the ritual kinship established in the Catholic Church to stablish themselves in the free universe of the region. With respect to the immediate after-abolition, it is understood that a significant migration from the rural areas of Espirito Santo to the city did not happen, neither for other states of Brazil. However, it was notice in newspaper analyses that the meanings of freedom and citizenship in the immediate posterior years to the abolition in Espirito Santo were found in dispute. Between renewed alliances, constructed or breached between ex-gentlemen and exslaves, many egresses of the captivity seemed to live a time between slavery and freedom. The social relations revealed conflicting, with arbitrary acts of ex-owners of slaves and local authorities that evidenced the difficulty part of society to accept the slaves as equal in rights and accept them in the free universe.